Peran Masjid Baiturrahman dalam Internalisasi Moderasi Beragama: Studi Fenomenologi Interpretatif - Muhasim (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2024)
The mosque is the center of Islamic civilization. The role of mosques in the education of the people is very important. Bergama moderation is very important to educate people in religion. Extremism as opposed to moderation endangers people in practicing their religion. The role of mosques is very much needed in educating people about the importance of religious moderation. This research uses a qualitative approach, using interpretive phenomenology methods. Purposive sampling is the method used in this study, with criteria: Baiturrahman mosque congregation, Takmir Masjid, Kyai or Ustadz,using semi-structured interview techniques, it was then analyzed with the Colaizzi model approach. The research produced 4 themes, namely Theme 1: mosques are active in cultivating national commitment Theme 2: Mosques play an active role in instilling tolerance Theme 3: mosques play an active role in instilling non-violence Theme 4: mosques play an active role in instilling adaptive attitudes towards culture.